Implementasi KTSP dalam Program Pembelajaran di PAUD Alif Pamijahan Bogor - Herlina Herlina (Fakultas Syariah IAIN Laa Roiba Bogor, 2020)
ABSTRACT This study aims to give ficturing the teachers and head scools of early childhood to improved quality of services in each early childhoods. This study uses is descriptive qualitative research. It is heald in Alif early childhood ( Kindergarden) at Pamijahan Bogor.The data was taken from observation,interview, documentation, and library studys. Based on the result of research, the implementation of KTSP from learning programs is maked improved tree asfect 1) curiculums developing of childrens 2) to establish a cooperation with school and parents with parenting programs 3) developing programs to get teacher make better in professionalism. Keyword : curiculums, Learning programs, early childhood